The role of two superoxide dismutase mRNAs in rye aluminium tolerance. (7th January 2015) - Sánchez‐Parra, B.; Figueiras, A. M.; Abd El‐Moneim, D.; Contreras, R.; Rouco, R.; Gallego, F. J.; Benito, C.; Martinoia, E.
Abstract Aluminium (Al) is the main factor that limits crop production in acidic soils. There is evidence that antioxidant enzymes such as superoxide dismutase (SOD) play a key role against Al‐induced oxidative stress in several plant species. Rye is one of the most Al‐tolerant cereals and exudes both citrate and malate from the roots in response to Al. The role of SOD against Al‐induced oxidative stress has not been studied in rye. Al accumulation, lipid peroxidation, H2O2 production and cell death were significantly higher in sensitive than in tolerant rye cultivars. Also, we characterised two genes for rye SOD: ScCu/ZnSOD and ScMnSOD. These genes were located on the chromosome arms of 2RS and 3RL, respectively, and their corresponding hypothetical proteins were putatively classified as cytosolic and mitochondrial, respectively. The phylogenetic relationships indicate that the two rye genes are orthologous to the corresponding genes of other Poaceae species. In addition, we studied Al‐induced changes in the expression profiles of mRNAs from ScCu/ZnSOD and ScMnSOD in the roots and leaves of tolerant Petkus and sensitive Riodeva rye. These genes are mainly expressed in roots in both ryes, their repression being induced by Al. The tolerant cultivar has more of both mRNAs than the sensitive line, indicating that they are probably involved in Al tolerance.